2008
DOI: 10.1073/pnas.0802773105
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio parahaemolyticus orchestrates a multifaceted host cell infection by induction of autophagy, cell rounding, and then cell lysis

Abstract: The bacterial pathogen Vibrio parahaemolyticus utilizes a type III secretion system to cause death of host cells within hours of infection. We report that cell death is completely independent of apoptosis and occurs by a mechanism in which injection of multiple type III effectors causes induction of autophagy, cell rounding, and the subsequent release of cellular contents. Autophagy is detected by the appearance of lipidated light chain 3 (LC3) and by increases in punctae and vacuole formation. Electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 30 publications
7
119
3
1
Order By: Relevance
“…Interestingly, V. alginolyticus induces apoptosis during the process of T3SS-mediated cell death, whereas V. parahaemolyticus does not. In contrast to our findings, the T3SS1-mediated cell death of V. parahaemolyticus preserves the integrity of the host-cell nuclear membrane and does not activate caspase molecules (Burdette et al 2008;Zhou et al, 2009). This difference may be due to the inherent differences in the T3SS effectors of V. alginolyticus and V. parahaemolyticus, as there were some minor differences between the hypothetical regions encoding them ( Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Interestingly, V. alginolyticus induces apoptosis during the process of T3SS-mediated cell death, whereas V. parahaemolyticus does not. In contrast to our findings, the T3SS1-mediated cell death of V. parahaemolyticus preserves the integrity of the host-cell nuclear membrane and does not activate caspase molecules (Burdette et al 2008;Zhou et al, 2009). This difference may be due to the inherent differences in the T3SS effectors of V. alginolyticus and V. parahaemolyticus, as there were some minor differences between the hypothetical regions encoding them ( Supplementary Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…EPC cells infected with wild-type ZJO, DvscC or C-vscC, were stained with Hoechst 33258 (Sigma) at indicated time points post-infection as described by Burdette et al (2008). Cells were left untreated or were treated with 2 mM staurosporine (STS) as controls.…”
Section: T3ss Of V Alginolyticus Induces a Unique Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is possible that the wild-type strain (NY-4) and the other six strains used in the present study caused rapid cell death (within 4 h) by unrecognized effector protein(s) of T3SS1 that are absent in the strain used in previous studies (RIMD2210633; unavailable for the present study) and that this rapid cell death prevented detection of apoptosis in our study. Burdette et al (2008) also reported that host cell death induced by V. parahaemolyticus is independent of apoptosis.T3SSs are needle-like structures expressed on the surface of Gram-negative bacteria and upon contact with eukaryotic cells (Cornelis & Van Gijsegem, 2000;Cornelis, 2002Cornelis, , 2006Hueck, 1998;Mota & Cornelis, 2005). These structures become inserted into the cell membrane to create pores in the membrane surface (Neyt & Cornelis, 1999); these pores assist the translocation of effector proteins from bacteria into host cells (Neyt & Cornelis, 1999).…”
mentioning
confidence: 96%
“…Nevertheless, the clinical manifestation of vibriosis is consistent with an inflammatory response, including neutrophil recruitment to the site of intestinal infection (Qadri et al, 2003); this inflammatory response is more consistent with oncosis or pyroptosis than apoptosis or autophagy. Furthermore, Burdette et al (2008) have recently reported that V. parahaemolyticus induces autophagy in cell culture, but blocking this pathway does not block cell death. Thus, it is very likely that alternative pathways are primarily responsible for cell death.…”
mentioning
confidence: 99%